Molecular dynamics simulation of the M2 helices within the nicotinic acetylcholine receptor transmembrane domain: structure and collective motions (Biophysical Society, 2005)
Multiple nanosecond duration molecular dynamics (MD) simulations were performed on the transmembrane region of the Torpedo nicotinic acetylcholine receptor (nAChR) embedded within a bilayer mimetic octane slab. The M2 helices and M2-M3 loop regions were free to move whilst the outer (M1, M3, M4) helix bundle was backbone restrained. The M2 helices largely retain their hydrogen-bonding pattern throughout the simulation, with some distortions in the helical-end and loop regions. All of the M2 helices exhibit bending motions, with the hinge point in the vicinity of the central hydrophobic gate region (corresponding to residues L251 and V255). The bending motions of the M2 helices lead to a degree of dynamic narrowing of the pore in the region of the proposed hydrophobic gate. Calculations of Born energy profiles for various structures along the simulation trajectory suggest that the conformations of the M2 bundle sampled correspond to a closed conformation of the channel. Principal components analyses (PCA) of each of the M2 helices, and of the five-helix M2 bundle, reveal concerted motions that may be relevant to channel function. Normal mode analyses using the anisotropic network model (ANM) reveal collective motions similar to those identified by PCA.